2018
DOI: 10.1186/s13568-018-0600-9
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus affects fecal microbial composition of young hens as determined by 16S rRNA sequencing

Abstract: The gut microbiota play important roles in the degradation of chemical compounds of herbal medicines (HMs). However, little information regarding the interplay between HMs and the gut microbiota is available. Thus, the aim of this study was to investigate the composition of the fecal microbiota of young (age, 11 weeks) hens fed a conventional diet containing a crude Astragalus (0.5%) additive for 21 days (group A) vs. controls (group B) that were fed only conventional feed. The fecal contents of 14-week-old he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 56 publications
4
28
0
Order By: Relevance
“…The major flavonoids of Astragalus are 3-O-β- d -glucoside, 2′-hydroxy-3′,4′-dimethoxyisoflavane-7-O-β- d -glycoside, 7,3′-dihydroxy-4′-methoxyisoflavone, 7,3-dimer-capto-4,1-methoxyisoflavone, 3-dimercapto-7,4,1-methoxyisoflavone, and kumatakenin (Lv et al 2011 ; Xiao et al 2004 ). A recent study showed that crude extracts of Astragalus are anti-inflammatory (Kim et al 2013 ), anti-viral (Zhang et al 2018 ), immunostimulatory (Zhang et al 2017 ), promote growth performance (Li et al 2018 ) and affects fecal microbiota of young hens (Qiao et al 2018a ). In recent years, fermentation has become a powerful tool for producing biological materials, degrading macromolecular material into small molecules, reducing the side effects associated with herbs such as Aristolochia plants, and introducing medicinal effects through biological modification (Lin and Chiang.…”
Section: Introductionmentioning
confidence: 99%
“…The major flavonoids of Astragalus are 3-O-β- d -glucoside, 2′-hydroxy-3′,4′-dimethoxyisoflavane-7-O-β- d -glycoside, 7,3′-dihydroxy-4′-methoxyisoflavone, 7,3-dimer-capto-4,1-methoxyisoflavone, 3-dimercapto-7,4,1-methoxyisoflavone, and kumatakenin (Lv et al 2011 ; Xiao et al 2004 ). A recent study showed that crude extracts of Astragalus are anti-inflammatory (Kim et al 2013 ), anti-viral (Zhang et al 2018 ), immunostimulatory (Zhang et al 2017 ), promote growth performance (Li et al 2018 ) and affects fecal microbiota of young hens (Qiao et al 2018a ). In recent years, fermentation has become a powerful tool for producing biological materials, degrading macromolecular material into small molecules, reducing the side effects associated with herbs such as Aristolochia plants, and introducing medicinal effects through biological modification (Lin and Chiang.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that curcumincan be used as a feed additive to enhance the antioxidant properties of laying hens [14],and isoflavones in soybeans can be used as additives to increase progesterone secretion from chicken granulosa cells [15]. Probiotics have also been reported as feed additives to slow the rate of reproductive aging [16].Additionally,there are many studies that Chinese herbal medicine can be used as a safe feed additive, such as the effect of Astragalus membranaceus on the gut microbiota of laying hens [17]. Therefore, such natural additives have a broad prospect in animal production.…”
mentioning
confidence: 99%
“…The purchased Astragalus was crushed into powder and ltered with a 100-mesh lter for further studies. The fermentation of Astragalus was performed following the method reported in our previous publications with slight modi cation (Qiao et al 2018b). Brie y, dried Astragalus powder (7,500 g) was inoculated with L. plantarum (1×10 6 colony forming unit (CFU) per gram) with a water content of 45%, and Astralagus-L. plantarum mixtures were aliquot into 35 × 45-mm plastic lm bags.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have con rmed that the solid fermentation of Astragalus by L. Plantarum promotes the extraction yield of Astragalus active components and the production yield of organic acids (Qiao et al, 2018c). Further investigation showed that fermented Astragalus improves broiler growth performance, enhances serum antioxidant status, and reduces fecal pathogenic microbiota of broiler chickens (Qiao et al, 2018b).…”
Section: Introductionmentioning
confidence: 93%